2023
DOI: 10.3390/rs15215190
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Residual Terrain Modelling and the Equivalent Source Layer Method in Gravity Field Synthesis for Airborne Gravity Gradiometer Test Site Determination

Meng Yang,
Wei-Kai Li,
Wei Feng
et al.

Abstract: To calibrate airborne gravity gradiometers currently in development in China, it is urgent to build an airborne gravity gradiometer test site. The site’s selection depends on the preknowledge of high-resolution gravity and gradient structures. The residual terrain modelling (RTM) technique is generally applied to recover the short-scale gravity field signals. However, due to limitations in the quality and resolution of density models, RTM terrain generally assumes a constant density. This assumption can introd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…In recent years, advancements in gravity surveying techniques have led to the establishment of gravimeter and gradiometer test sites, one example being the Kauring Test Site in Australia [36]. In China, efforts are underway to develop the first airborne gravity gradiometer test site at the Wudalianchi Volcano National Geopark, primarily intended for calibrating and validating airborne gravimetric systems based on dense terrestrial gravity measurements as reported by Yang et al [37]. The vast dataset collected from these tasks holds promise for various geophysical and geological interpretations.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, advancements in gravity surveying techniques have led to the establishment of gravimeter and gradiometer test sites, one example being the Kauring Test Site in Australia [36]. In China, efforts are underway to develop the first airborne gravity gradiometer test site at the Wudalianchi Volcano National Geopark, primarily intended for calibrating and validating airborne gravimetric systems based on dense terrestrial gravity measurements as reported by Yang et al [37]. The vast dataset collected from these tasks holds promise for various geophysical and geological interpretations.…”
Section: Introductionmentioning
confidence: 99%